Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/1096-9861(20000731)423:3<452::aid-cne8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide/Cyclic GMP pathway attenuates ATP-evoked intracellular calcium increase in supporting cells of the guinea pig cochlea

Abstract: We demonstrate here that nitric oxide (NO) attenuates ATP-evoked calcium transients in Deiters' and Hensen's cells, "supporting" (nonsensory) cells of the guinea pig cochlea, by means of activation of soluble guanylyl cyclase and protein kinase G. The enzymatic activities associated with the nitric oxide/cGMP/protein kinase G pathway had previously been demonstrated to be present in Deiters' and Hensen's cells. We now isolate these cells and measure changes in intracellular free calcium by using the calcium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 65 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…They contain microfilaments and microtubules and have primarily been considered a structural reinforcement of the neurosensory epithelium. More recent speculation, however, links these cells to dynamic structural changes (Dulon, 1994; Flock et al, 1999) and calcium‐based regulatory processes in the inner ear (Matsunobu and Schacht, 2000). Deiters' cells are innervated (Nadol and Burgess, 1994; Burgess et al, 1997; Fechner et al, 1998) yet the transmitters and receptors at these synapses are not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They contain microfilaments and microtubules and have primarily been considered a structural reinforcement of the neurosensory epithelium. More recent speculation, however, links these cells to dynamic structural changes (Dulon, 1994; Flock et al, 1999) and calcium‐based regulatory processes in the inner ear (Matsunobu and Schacht, 2000). Deiters' cells are innervated (Nadol and Burgess, 1994; Burgess et al, 1997; Fechner et al, 1998) yet the transmitters and receptors at these synapses are not known.…”
mentioning
confidence: 99%
“…Deiters' cells are innervated (Nadol and Burgess, 1994; Burgess et al, 1997; Fechner et al, 1998) yet the transmitters and receptors at these synapses are not known. Intracellular free calcium [Ca 2+ ] i in Deiters' cells is regulated by ATP (Dulon et al, 1993) and nitric oxide (Matsunobu and Schacht, 2000). In the present study, we investigate the effect of ACh on [Ca 2+ ] i in isolated Deiters' cells of the guinea pig cochlea and characterize the ACh effect pharmacologically…”
mentioning
confidence: 99%
“…Del Punta et al (10) showed that there is no increase in the cGMP production with or without GC after the incubation of Leydig cells with the NO donor DEA/NO. Matsunobu and Schacht (27) showed a decrease in intracellular [Ca 2+ ] when cochlear cells were treated with DEA/NO, SNP, and 8Br-cGMP, and an increase when GC was blocked by LY83583. However, Khurana et al (28) showed that atrial natriuretic factor (ANF), cerebral natriuretic factor (CNF) and type C natriuretic peptide (CNP) augmented the GC activity and cGMP in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because Deiters' cells can also be depolarized by ATP or acetylcholine [4,6], K + current-induced prompt repolarization may be needed to be ready for the next stimulation. The presence of the different types of outward rectifying K + currents from our results suggests that the modulating procedure may be precise and complex in Deiters' cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium concentration was increased by the extracellular application of acetylcholine to Deiters' cells and this increase was inhibited by strychnine suggesting the presence of alpha 9 acetylcholine receptor [4]. Furthermore, extracellular ATP could increase intracellular calcium ion and this increase was inhibited by nitric oxide through nitric oxide/cyclic GMP pathway in Deiters' and pillar cells [5,6]. Active and reversible movement was also observed in isolated Deiters' cells by increased intracellular calcium [7,8] and supporting cells in the organ of Corti in vivo by intense sound [9].…”
Section: Introductionmentioning
confidence: 99%